Robotic solution for the arrangement of tables and chairs - Ng, Ye Han (2018)
In the recent years, there had been an increasing trend in the use of the autonomous robot in the service industry. The use of robot has helped reduce the workload of human and provide consistency in the task performed. This project focus on developing a modular platform that will be loaded onto a mobile robot to provide an automatic solution for the arrangement of table and chair. The modular platform made use of the concept of four-bar linkage mechanism to carry the table and chair. Linear actuator and electromagnet were also used to automate the folding operation of the arm link, thus allowing the whole process to become fully automated. This report will include the design process for the development of the modular platform. The comparison was made between the new and old lifter design, and calculation was made to ensure safe operation of the modular platform.